Elevated H3K27ac in aged skeletal muscle leads to increase in extracellular matrix and fibrogenic conversion of muscle satellite cells. Issue 5 (20th July 2019) - Zhou, Jiajian; So, Karl K.; Li, Yuying; Li, Yang; Yuan, Jie; Ding, Yingzhe; Chen, Fengyuan; Huang, Yile; Liu, Jin; Lee, Wayne; Li, Gang; Ju, Zhenyu; et al.
Abstract: Epigenetic alterations occur in various cells and tissues during aging, but it is not known if such alterations are also associated with aging in skeletal muscle. Here, we examined the changes of a panel of histone modifications and found H3K27ac (an active enhancer mark) is markedly increased in aged human skeletal muscle tissues. Further analyses uncovered that the H3K27ac increase and enhancer activation are associated with the up‐regulation of extracellular matrix (ECM) genes; this may result in alteration of the niche environment for skeletal muscle stem cells, also called satellite cells (SCs), which causes decreased myogenic potential and fibrogenic conversion of SCs. In mice, treatment of aging muscles with JQ1, an inhibitor of enhancer activation, inhibited the ECM up‐regulation and fibrogenic conversion of SCs and restored their myogenic differentiation potential. Altogether, our findings not only uncovered a novel aspect of skeletal muscle aging that is associated with enhancer remodeling but also implicated JQ1 as a potential treatment approach for restoring SC function in aging muscle. Abstract : H3K27ac is markedly increased in human or mouse muscle during aging, which leads to the enhancer activation and subsequent up‐regulation of ECM genes. It causes the alteration of SC niche and fibrogenic conversion of SCs. In mice, treatment of aging muscles with JQ1, an inhibitor of enhancer activation, reduced the fibrogenesis and improved the myogenic potential of SCs.